DOI: 10.11606/d.23.2019.tde-02122019-111213
|View full text |Cite
|
Sign up to set email alerts
|

Terapia de fotobiomodulação na disfunção temporomandibular: Resultados preliminares em dor e movimentos mandibulares

Abstract: Gostaria de agradecer também a outros docentes da FOUSP que impactaram especialmente minha formação como pesquisadora e docente. Prof a. Dr a. Maine Skelton, Prof a. Dr a. Maria Gabriela Haye Biazevic, Prof a. Dr a. Adriana Lira-Ortega, Prof a. Dr a. Márcia Martins Marques e Prof a. Dr a. Alyne Simões Gonçalves: cada uma de vocês cruzou o meu caminho em etapas distintas, me marcando de maneira significativa, me inspirando e fortalecendo para este momento... Este pequeno agradecimento é para dizer que que levo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 142 publications
(266 reference statements)
0
3
0
Order By: Relevance
“…Zwiri et al ( 2020) said that patients with TMD suffer from continuous pain for a long time, even after conventional treatment. Jing et al (2021) and Dantas et al (2019) had promising results up to one month after treatment with d1 laser therapy (energy density ranging from 0 to 10 J/cm2), which also performed better than than the placebo and other laser groups. Dantas et al (2019) reported that all tested photobiomodulation therapy protocols were able to reduce pain on palpation in the superficial masseter muscle and TMJ of individuals with TMD.…”
Section: Results Analysismentioning
confidence: 91%
See 2 more Smart Citations
“…Zwiri et al ( 2020) said that patients with TMD suffer from continuous pain for a long time, even after conventional treatment. Jing et al (2021) and Dantas et al (2019) had promising results up to one month after treatment with d1 laser therapy (energy density ranging from 0 to 10 J/cm2), which also performed better than than the placebo and other laser groups. Dantas et al (2019) reported that all tested photobiomodulation therapy protocols were able to reduce pain on palpation in the superficial masseter muscle and TMJ of individuals with TMD.…”
Section: Results Analysismentioning
confidence: 91%
“…Jing et al (2021) and Dantas et al (2019) had promising results up to one month after treatment with d1 laser therapy (energy density ranging from 0 to 10 J/cm2), which also performed better than than the placebo and other laser groups. Dantas et al (2019) reported that all tested photobiomodulation therapy protocols were able to reduce pain on palpation in the superficial masseter muscle and TMJ of individuals with TMD. Vallejo et al (2019) corroborate this in part, as after testing various low-intensity laser application protocols, they were unable to find scientific evidence that one of them was superior to the others, and all had good results.…”
Section: Results Analysismentioning
confidence: 91%
See 1 more Smart Citation